Ecofriendly strategy based on the combination of inoculation with plant growth-promoting bacteria and reduced nitrate doses boosts the valorization of purple cauliflowers - Collado-González, Jacinta; Piñero, María Carmen; Otálora, Ginés; González, Yamara; López-Marín, Josefa; del Amor, Francisco M. (Frontiers in Plant Science, 2025)
IntroductionThe reduced N doses in plant fertilization, combined with the influence of plant growth-promoting bacteria (PGPB), to obtain ecofriendly crops and their derived products can be a significant challenge. Purple cauliflower is an exotic variety that can generate higher profits for farmers and greater interest among consumers seeking novel and healthy foods. Purple cauliflower florets are edible, while the leaves are discarded because they are by-products.MethodsThe aim of this research was to investigate the combined effect of PGPB (Azotobacter salinestris strain CECT9690) and three different N doses supplied in the nutrient solution (30%, 60%, and 100%) on plant growth and the quality of florets and by-products. Plant height, total shoot and floret weight, and % dry weight in florets and leaves were improved by A. salinestris inoculation under limited doses of N.Results and discussionThe sugar content in the leaves of plants grown with a limited N dose (30%) and inoculated with PGPB increased by 51% compared to the control. PGPB inoculation increased proteins in the leaves (by 30% with 100% N supply, 33% with 60% N supply, and 16% with 30% N supply). Additionally, PGPB inoculation enhanced potassium (26%) and iron (34%) in leaves of plants under limited N supply. These findings indicate that the combined use of reduced N supply and PGPB inoculation may be considered an ecofriendly strategy to enhance the growth and quality of purple cauliflower, while boosting the valorization of its by-products.